Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the relation between $a, b, c, d$ if the roots of $ax^3+bx^2+cx+d=0$ are in geometric progression.

By considering $(\alpha+\beta)(\beta+\gamma)(\alpha+\gamma)$ show that the above cubic equation has two roots equal in size but opposite in sign if and only if $ad=bc$.

I can do the second part if I am given some hints on the first. I can use $\beta$ as the middle root and make $\alpha=\beta/r$ and $\gamma=r \times \beta$, but haven't got anywhere so far.

share|improve this question

2 Answers 2

The monic polynomial with roots $\beta/r,\beta, r\beta$ is $$ x^3-\beta\left(1+r+\frac1r\right) x^2+\beta^2\left(1+r+\frac1r\right)x-\beta^3$$ We find $\beta=-\frac cb$ and $\beta^3=-\frac da$, hence $$db^3=ac^3$$ as necessary condition. Why is it also sufficient? What additional condition(s) would we need if we wanted the roots to be real?

share|improve this answer

If $\alpha, \beta, \gamma$ are the roots of $ax^3+bx^2+cx+d=0$

Using Vieta's Formulas, $$\alpha+\beta+\gamma=-\frac ba, \alpha\beta+\beta\gamma+\gamma\alpha=\frac ca,\alpha\beta\gamma=-\frac da$$

If $\alpha,\beta,\gamma$ are in Geometric Progression, $\frac\beta\alpha=\frac\gamma\beta$ is constant $=r$(say). Clearly, $\alpha r\ne 0$

$\implies \beta=\alpha r, \gamma=\beta r=\alpha r^2$

$$\implies \alpha+\alpha r+\alpha r^2=-\frac ba\implies \alpha(1+r+r^2)=-\frac ba$$

$$\alpha\alpha r+\alpha r\alpha r^2+\alpha r^2\alpha=\frac ca\implies \alpha^2 r(1+r+r^2)=\frac ca$$

$$\alpha\alpha r\alpha r^2=-\frac da\implies \alpha^3 r^3=-\frac da$$

So, $$\frac{\alpha^2 r(1+r+r^2)}{\alpha(1+r+r^2)}=\frac{\frac ca}{-\frac ba}\implies \alpha r=-\frac cb \text{ if }1+r+r^2\ne0$$

Then, $$\left(-\frac cb\right)^3=-\frac da\implies b^3d=c^3a$$

If $1+r+r^2=0,$

$b=c=0$ and $r=\frac{-1\pm\sqrt3}2$ i.e., r is a complex cube root of $1$

So, the equation reduces to $ax^3+d=0$ whose roots are $\left(-\frac da\right)^\frac13,\left(-\frac da\right)^\frac13r, \left(-\frac da\right)^\frac13r^2$.

So, we don't find any relationship among $a,b,c$ and $d$ here.


In the 2nd case, let us find the equation whose roots are $\alpha+\beta,\beta+\gamma, \gamma+\alpha$ using the Transformation of Equations.

If $y=\alpha+\beta=\alpha+\beta+\gamma-\gamma=-\frac ba-\gamma\implies \gamma=-\left(y+\frac ba\right)$

As $\gamma$ is a root of the given equation, $-a\left(y+\frac ba\right)^3+b\left(y+\frac ba\right)^2-c\left(y+\frac ba\right)+d=0$

On simplification, $$ay^3+(\cdots)y^2+(\cdots)y^2+\frac{bc-ad}a=0$$ whose roots are $\alpha+\beta,\beta+\gamma, \gamma+\alpha$

Using Vieta's Formulas again, $(\alpha+\beta)(\beta+\gamma)(\gamma+\alpha)=\frac{ad-bc}{a^2}$

If among $\alpha,\beta,\gamma$ two have same absolute value but opposite sign, $(\alpha+\beta)(\beta+\gamma)(\gamma+\alpha)=0\implies ad=bc$ (the condition is necessary)

Sufficiency: Again, if $ad=bc,$ $\frac ab=\frac cd=t$(say,) so $a=bt,c=dt$

Then the equation becomes $$btx^3+bx^2+dtx+d=0\implies bx^2(tx+1)+d(tx+1)=0$$

So, $$(tx+1)(bx^2+d)=0$$ One root is $-\frac1t$ What about the others?

share|improve this answer
    
$x=\sqrt{-d/b}$ which is not really $1/t$, the thing we need? –  bbr4in Feb 1 '13 at 21:59
    
@user52187, I left it for you to find the two roots other than $-\frac1t=-\frac ba=-\frac dc$ to prove the proposition as it is after all a 'homework'. –  lab bhattacharjee Feb 2 '13 at 3:27
    
So is what I wrote incorrect? –  bbr4in Feb 3 '13 at 22:09
    
@user52187, no. You are right when you say $\frac1t\ne \pm\sqrt{-\frac db}$. But 'homework' is not supposed to be answered fully here as my last comment has pointed out. –  lab bhattacharjee Feb 4 '13 at 3:29

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.